Analisis Penerapan Media Puzzle pada Pembelajaran Matematika Materi Perkalian Kelas II - Lutfiana, Lutfiana; Kusumaningsih, Widya; Nur Setyaningsih, Ariani (Universitas Ngudi Waluyo, 2024)
Abstract The lack of students' understanding in multiplication, revealed through observations, can have negative consequences on the comprehension of multiplication concepts that should have been mastered. This is attributed to the absence of the use of instructional media by teachers, ultimately leading to a decline in students' learning outcomes. This study aims to evaluate the implementation of puzzle media in mathematics learning, particularly in the multiplication topic, in Supriyadi Elementary School's 2nd-grade class. Using a qualitative descriptive method with data collection through interviews, observations, tests, and documentation, the study achieves two main objectives. First, to assess the extent to which puzzle media is integrated into mathematics learning and identify its impact on students' understanding of multiplication concepts. Second, to evaluate students' ability to calculate multiplication. The research subjects consist of 27 students. The results of the study indicate that 2nd grade students at Supriyadi Elementary School have shown positive progress in multiplication calculations, and the implementation of puzzle media has proven effective in enhancing their understanding of the subject. This research makes a significant contribution to understanding the effectiveness of puzzle media in the context of multiplication mathematics learning in the 2nd grade, as well as the level of students' ability to master these concepts. The students are highly enthusiastic and enjoy playing puzzles. Based on the research and discussions regarding the use of puzzles in mathematics learning, especially in multiplication for the 2nd grade, it can be concluded that the utilization of puzzle media has a more positive impact. Students can comprehend and analyze problems effectively, and they can also design, plan, and seek solutions before checking their answers. Abstrak Kurangnya pemahaman siswa dalam memahami perkalian, yang terungkap melalui observasi, dapat memiliki konsekuensi negatif pada pemahaman materi perkalian yang seharusnya sudah dikuasai. Hal ini disebabkan oleh tidak adanya penggunaan media pembelajaran oleh guru, yang pada akhirnya berdampak pada penurunan hasil belajar siswa. Penelitian ini bertujuan untuk mengevaluasi penerapan media puzzle dalam pembelajaran matematika, khususnya pada materi perkalian, di kelas 2 SD Supriyadi. Melalui metode deskriptif kualitatif dengan pengumpulan data melalui wawancara, observasi, tes, dan dokumentasi, penelitian ini mencapai dua tujuan utama. Pertama, menilai sejauh mana media puzzle diintegrasikan dalam pembelajaran matematika dan mengidentifikasi dampaknya pada pemahaman siswa terhadap konsep perkalian. Kedua, mengevaluasi kemampuan siswa dalam menghitung perkalian. Subjek penelitian berjumlah 27 siswa. Hasil penelitian menunjukkan bahwa siswa kelas 2 di SD Supriyadi telah menunjukkan kemajuan positif dalam menghitung perkalian, dan penerapan media puzzle terbukti efektif dalam meningkatkan pemahaman mereka terhadap materi tersebut. Penelitian ini memberikan kontribusi penting terhadap pemahaman efektivitas media puzzle dalam konteks pembelajaran matematika perkalian di kelas 2 serta tingkat kemampuan siswa dalam menguasai konsep tersebut. Para siswa sangat senang dan menikmati bermain puzzle. Berdasarkan penelitian dan pembahasan tentang penggunaan puzzle dalam pembelajaran matematika materi perkalian untuk kelas 2, dapat disimpulkan bahwa pemanfaatan media puzzle memberikan dampak yang lebih positif. Siswa mampu memahami dan menganalisis masalah dengan baik, mereka juga dapat merancang, merencanakan, dan mencari solusi sebelum memeriksa jawaban mereka.